The Effects of Household Accounting on Expenses Base on The Sufficiency Economy Philosophy The Integrated Project for The Solving Poverty Problem in Rural Areas - Watanakanjana et al., Chantana (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The purpose of this paper are: 1) To compare pre and post knowledge with household accounting of people of prototype community, the Integrated Project. 2) To study attitude of household accounting which affected expenditures base on the sufficiency economy philosophy, the integrated project for the solving poverty problem in rural areas for people of prototype community. 3) To study the acceptance of household accounting which affected expenditures base on the sufficiency economy philosophy, the integrated project for the solving poverty problem in rural areas for people of prototype community. The sampling method was applied by purposive sampling. The data were collected from head of household, total 74 respondents. The research instruments were consisted of questionnaire, observation form, household accounting form and performance assessment form. The statistics used for data analysis were frequency percentage and t-test. The research finding revealed as follows; 1) The comparison results of household accounting knowledge of people in prototype community, the Integrated Project found that average score of posttest was higher than pretest at statistic significant level .01 2) The attitude of household accounting found that the highest average score at 4.55 related to the community encouragement in the training of household accounting. The second average score at 4.01 involved with the training participation of relevant organizations in household accounting. Finally, the lowest average score at 2.40 was the complexity of household accounting process. 3) The household accounting acceptance has collective behavior which was shown by returning the household account books total 86.49%. Furthermore, the result of household accounting affected expenses base on the sufficiency economy philosophy have shown by average score from high to low as the following; the reducing expense goal was 37.84% and the result was 38.01%. The avoiding expense goal was 31.08% and the result was 30.41%. In addition, the quitting expense goal was 27.70% and the result was 28.21%. Article history : Received 2 February 2020 Revised 6 March 2020 Accepted 9 March 2020 SIMILARITY INDEX = 0.00 %